Roles of e-Management Systems in School Administration to keep pace with Vision 2030 of KSA in Makkah (2022) - Alotaibi, Badriah Mohammad Muner (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aims at defining the electronic administration and its role in developing the administrative process in the public schools, measuring the impact of implementing its systems on the development of the administrative work and the performance of the administrative staff in the public schools, identifying obstacles and presenting some recommendations to face these obstacles. To achieve this, the researcher used the descriptive, analytical method, relying on the questionnaire tool that was distributed to a random sample of 100 principals and administrators in public schools in Makkah. The data are collected from randomly different schools to measure the extent to which electronic management is applied. In order to achieve the objectives of the study, a questionnaire was developed, consisting of two parts; the first part about the personal information of each employee, and the second section consists of seven axes for the effect of electronic management on performance. The results of the study showed the application of electronic management in schools in the city of Mecca, where most of the results were limited to the mean values (3.40-4.19), which indicate that all respondents agreed that they have knowledge of electronic management systems. Electronic management systems helped develop administrative work and improve the performance of employees. In government schools, the effectiveness of electronic management systems and the speed of their performance. Whereas everyone strongly supports and agrees with a high degree between (4.20-5.00) that the use of electronic management contributes to achieving Vision 2030. However, it was found that there are obstacles in the lack of facilities that schools need to support electronic management systems, as well as challenges facing the application of electronic management systems. Through the result that appeared (2.60-3.39), the majority was neutral. Through these results, I find that a number of recommendations and proposals must be presented, the most important of which are: Providing modern tools and devices that suit this development, ensuring the security and protection of electronic information, intensifying courses and programs in the field of electronic management, and clarifying the obstacles that could cause the failure of this management.